Tekstualisasi dan Kontektualisasi Hukum Islam dalam Al-Quran Dan Hadis: Textualization and Contextualization of Islamic Law: Perspectives from the Qur’an and Hadith - Sri Karmila Dol; Muhammad Amri; Darussalam Syamsuddin (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
The study of Islamic teachings cannot be separated from two main sources: The Qur'an and Hadith. Both are normative foundations in the life of Muslims that contain universal, spiritual and social values. However, the interpretation of these religious texts is not single and final. There are dynamics of understanding that develop from time to time, especially when the texts are faced with different social, cultural and historical contexts. This article aims to examine the process of textualization of Islamic teachings, namely how the Qur'an and Hadith are transmitted, codified and interpreted as normative texts. Furthermore, this article also examines the process of contextualization, which is an attempt to understand and apply these teachings in accordance with contemporary social realities without ignoring the basic values of Islam. Through a hermeneutic approach and historical criticism, this article finds that the contextual interpretation of Islamic teachings actually strengthens the relevance of the Qur'an and Hadith in responding to the challenges of the times. Thus, textual and contextual approaches are not contradictory, but complementary in formulating Islamic teachings that are alive and transformative.